Regional Economic Development Planning Based on the Agriculture, Forestry, and Fisheries Sectors to Reduce Poverty in the Regencies and Municipalities of West Nusa Tenggara Province, Indonesia (2019–2023) - I Gusti Wayan Astradana; Hailuddin Hailuddin; Iwan Harsono (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study is motivated by the substantial contribution of the agriculture, forestry, and fisheries sectors to the Gross Regional Domestic Product (GRDP) of West Nusa Tenggara (NTB) Province, accounting for approximately 22–23%, which has not been accompanied by a significant reduction in poverty. The study aims to analyze the potential of these three sectors and formulate effective regional economic development strategies to reduce poverty. A descriptive qualitative approach was employed through in-depth interviews, observations, and document analysis of regional development planning documents. The findings indicate that the potential of the primary sectors has not been optimally utilized due to low value-added activities and limited downstream industrial development. Furthermore, policy implementation is constrained by inadequate infrastructure, limited data availability, and insufficient human resource capacity and technological capability. The recommended strategies include modernizing the primary sectors, strengthening cross-sectoral coordination, and accelerating downstream development to increase value added and improve community income, thereby contributing to sustainable poverty reduction.